2008
DOI: 10.1038/eye.2008.143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the change in accommodation amplitude in subjects with pseudoexfoliation

Abstract: bstractPurpose To evaluate the changes in accommodation amplitude in cases with pseudoexfoliation. Materials and methods Twenty-nine eyes having pseudoexfoliation and 37 normal eyes aged between 40-60 years were included in the study. After ophthalmic examination, accommodation amplitude was measured using Powerrefractor II. Besides, axial length, anterior chamber depth, and lens thickness was measured by A-scan ultrasonography. The results obtained were evaluated by independent samples' t-test. Results There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…In a study by Yavas et al, there was no change in AL, LT, and ACD in eyes with PXE as compared to normal eyes, [8] the findings of which were similar to the results of the present study, except a significant increase in AL was observed in eyes with PXE.…”
Section: Discussionsupporting
confidence: 81%
“…In a study by Yavas et al, there was no change in AL, LT, and ACD in eyes with PXE as compared to normal eyes, [8] the findings of which were similar to the results of the present study, except a significant increase in AL was observed in eyes with PXE.…”
Section: Discussionsupporting
confidence: 81%
“…minus lens technique and infra-red photorefractor technique respectively) [12] . However, this study noted the difference of amplitude of accommodation for three different room illuminations at 30° downward gaze in compare to Yavas et al's study where they have viewed the difference of amplitude of accommodation at primary gaze [12] . There is no previous study which can contradict or support our study for amplitude of accommodation at three different illumination level and gender.…”
Section: Methodsmentioning
confidence: 99%
“…uses different techniques to measure amplitude of accommodation (i.e. minus lens technique and infra-red photorefractor technique respectively) [12] . However, this study noted the difference of amplitude of accommodation for three different room illuminations at 30° downward gaze in compare to Yavas et al's study where they have viewed the difference of amplitude of accommodation at primary gaze [12] .…”
Section: Methodsmentioning
confidence: 99%
“…In a different study mechanical restriction of pupil has been attributed to the adherent material between pigment epithelium of the iris and anterior lens capsule [ 17 , 18 ]. Accommodation amplitude of the eyes with EXS has also been found to be decreased compared to healthy subjects [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accommodation amplitude has been shown to be related with a pupil diameter and smaller pupil size leads to an increase in the measured accommodation amplitude [ 21 ]. Yavas et al did not find any correlation between accommodation and pupil diameter in EXS eyes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%